Extensive muscle spasms after unprovoked dog bite: Is it rabies? - Aulakh, Roosy; Singh, Jasmine (Indian Journal of Case Reports, 2018)
We report a 7-year-old incompletely immunized male child who presented with intermittent dyspnea, fever, and extensive muscle spasms following an alleged history of unprovoked Category III dog bite 20 days back with inadequate post-exposure prophylaxis. This case highlights the importance of detailed clinical evaluation including minor signs such as trismus, persistent tetanic muscle contraction in intervening period between muscle spasms and preservation of normal sensorium in the absence of aerophagia and hydrophobia in ruling out a possible diagnosis of rabies in this child, and establishment of diagnosis of less sinister treatable disease with better prognosis.